Analisa Keberadaan Jamur Trichophyton rubrum pada Kuku Kaki Petugas Kebersihan Dinas Lingkungan Hidup Surabaya - Mitra Putri Mandiri; Retno Sasongkowati; Anita Dwi Anggraini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Sanitation workers play a vital role in maintaining environmental cleanliness. However, many of them neglect their personal hygiene. Sanitation workers are professions that regularly wear closed shoes for long periods,the humid, hot, and dirty work environment promotes fungal infections in toenails, known as onychomycosis. The purpose of this study is to analyze the presence of the fungus Trichophyton rubrum on the toenails of the sanitation workers of the Surabaya Environmental Service Department. This study is a descriptive laboratory observation. The research was conducted from February 23 to March 13, 2024. Sample collection took place at Surabaya Environmental Service Department, and the study carried out at Mycology Laboratory of the Medical Laboratory Technology Department, Poltekkes Kemenkes Surabaya. The samples in this study consisted of toenails from 30 sanitation workers members. The examination was conducted using the culture method on SDA media, incubated for 7-14 days, followed by macroscopic and microscopic observations. The results showed that 2 samples were positive for Trichophyton rubrum (6.7%), 23 samples were positive for Aspergillus sp., (76.7%), 4 samples were positive for Rhizopus sp., (13.3%), and 1 sample was positive for Penicillium sp., (3.3%). The conclusion is, out of 30 samples, 2 individuals (6.7%) tested positive for Trichophyton rubrum, while the remaining 28 samples (93.3%) tested negative for Trichophyton rubrum.